INTOLERANCE OF UNCERTAINTY AND PSYCHOLOGICAL ADJUSTMENT AMONG COLLEGE STUDENTS: DOOMSCROLLING AND HOPELESSNESS AS MULTIPLE MEDIATORS - Kutuk, Hasan; Okur, Sinan; Satici, Seydi ahmet (ACADEMIA, 2025)
Psychological adjustment, which is one of the most important concepts for the mental health of individuals, has many determinants. This research aimed to examine the role of doomscrolling and hopelessness in the relationship between intolerance of uncertainty and psychological adjustment. 406 college students completed four scales measuring psychological adjustment, intolerance of uncertainty, doomscrolling, and hopelessness. The correlation analysis results demonstrated that hopelessness, doomscrolling, and intolerance of uncertainty were negatively related to psychological adjustment. Moreover, the association between intolerance of uncertainty and psychological adjustment was found to be partially mediated by doomscrolling and hopelessness, according to structural equation modeling analysis. The findings enrich the literature on psychological adjustment, which is important for human mental health.
Keywords: intolerance of uncertainty; psychological adjustment; doomscrolling; hopelessness; PSYCHOMETRIC PROPERTIES; CERTAINTY; FUTURE; SCALE; LIFE; Psychology